2019
DOI: 10.1002/esp.4634
|View full text |Cite
|
Sign up to set email alerts
|

Imprints of wave climate and mean sea level variations in the dynamics of a coastal spit over the last 250 years: Cap Ferret, SW France

Abstract: In coastal areas, sea level rise (SLR) and changing wave climates are expected to be the main oceanic drivers of shoreline adjustments. These drivers have been shown to vary on a wide spectrum of spatial and temporal scales. Nonetheless, a general rule about how this variability impacts global shorelines remains to be articulated. Here, we discuss the impacts of wave climate changes and SLR on the evolution of a barrier spit-inlet system over the last 250 years. The distal end of the Cap Ferret barrier spit, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 79 publications
(99 reference statements)
1
12
0
Order By: Relevance
“…The sandspit is part of a 230-km sandy shore, interrupted by the Bay of Arcachon's tidal inlet [29]. The inlet borders the spit's southern extremity and both have interacted in such way that the spit has been retreating since 1972 [30]. In this process, the shore loses an estimated 46,000 m 3 of sand per year, on average since 1986.…”
Section: Study Areamentioning
confidence: 99%
“…The sandspit is part of a 230-km sandy shore, interrupted by the Bay of Arcachon's tidal inlet [29]. The inlet borders the spit's southern extremity and both have interacted in such way that the spit has been retreating since 1972 [30]. In this process, the shore loses an estimated 46,000 m 3 of sand per year, on average since 1986.…”
Section: Study Areamentioning
confidence: 99%
“…As it develops, the hook extends towards a zone of lower energy where sediment transport decreases, causing cessation of hook elongation. (3) Longshore transport variations (modulated by wave height) at seasonal to inter‐annual timescales (Allard et al ., 2008; Petersen et al ., 2008; Nahon et al ., 2019). Energetic swells seem to cause massive sand accumulation and spit elongation, whereas less energetic swells appear to be responsible for minor accumulation and spit curvature.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to other inlets, whose morphology exhibits a cyclical behavior (e.g., Nahon et al, 2019, Lenstra et al, 2019, the Tagus Estuary showed an apparent stability for over a century, followed by a persistent trend in the past seven decades. The persistent erosion of the Cachopo Sul raises concerns about the future evolution of this bank.…”
Section: Foreseeable Evolutionmentioning
confidence: 65%
“…Finally, the intense sediment dynamics at tidal inlets can affect the adjacent coast (Fitzgerald, 1984). Because these dynamics result from a delicate balance between tidal and wave action, tidal inlets can act alternately as sources and sinks of sediments (Nahon et al, 2019). The morphological evolution of tidal inlets and the adjacent beaches is thus often closely linked.…”
Section: Introductionmentioning
confidence: 99%